Treatment patterns and survival in an exhaustive French cohort of pazopanib-eligible patients with metastatic soft tissue sarcoma (STS). Issue 1 (December 2017) - Ray-Coquard, Isabelle; Collard, Olivier; Ducimetiere, Françoise; Laramas, Mathieu; Mercier, Florence; Ladarre, Nadine; Manson, Stephanie; Tehard, Bertrand; Clippe, Sébastien; Suchaud, Jean-Philippe; Stefani, Laetitia; Blay, Jean-Yves
Abstract Background The French EMS study prospectively collected exhaustive data from STS patients diagnosed in the Rhone-Alpes region from 2005 to 07. Methods The database included diagnosis/histology, surgery, radiotherapy, systemic treatments and treatment response. Treatment patterns and outcomes of patients with metastatic disease, excluding adipocytic sarcoma and GIST were analyzed. Results Of 888 total patients, 145 were included based on having metastatic disease and appropriate subtypes. All patients received treatment with systemic therapy being most common (74%, n  = 107), followed by radiotherapy (30%, n  = 44) and surgery (23%, n  = 33). Doxorubicin, alone or in combination, was the most common first line systemic therapy (65%, n  = 46). Drugs without license in sarcoma were used in 38–83% of treatments depending on treatment line. 24% of frontline patients demonstrated an objective response, decreasing to 11% objective responses in second line but no responses were documented beyond second line, with median PFS declining with each additional line. Median PFS also declined in patients receiving surgery compared to those receiving no surgery (8–15 m vs 5 m). Median OS from metastatic diagnosis for patients receiving systemic therapy was double that of patients without systemic treatment (24 m vs 12 m, p  = 0.007). Conclusions Outcomes in this population were poor and declined with successive treatment. However, results suggest that further anticancer therapies in recurrent sarcoma might be beneficial.